Assessment of Serum Vitamin D Levels among Patients Attending Institute of Nuclear Medicine and Allied Sciences (INMAS), Sylhet, Bangladesh - Kamrun Nahar; Muhammad Sirazul Munir (International Journal of Human and Health Sciences (IJHHS), 2026)
Deficiency of vitamin D is a major health problem globally and is associated with different chronic diseases. The aim of this study was to assess serum vitamin D levels according to age and gender at the Institute of Nuclear Medicine and Allied Sciences (INMAS), Sylhet, Bangladesh. A total 173 patients attending INMAS, Sylhet, for serum vitamin D levels evaluation from July 2022 to June 2023 were included in the study. Patients with vitamin D replacement therapy were excluded from this study. Serum viamin D was determined by Siemens ADVA Centaur XPT chemiluminescence immunoassay (CLIA) System. Patients were classified as vitamin D-deficient, insufficient or sufficient based on the serum vitamin D concentrations of 30 ng/mL, respectively. Among study subjects 122 (70.5%) were female and 51(29.5%) were male. The age of the patients ranged from 05 to 81 years with the mean age was 40.24±15.38 years. Regarding the prevalence of vitamin D deficiency among the study participants, 73.41% were found to be deficient in vitamin D, while 15.03% had insufficient and 11.56% had sufficient levels of vitamin D. Vitamin D deficiency was highly prevalent in the age group of 0–18 years (88.88%), followed by 37–54 (78.57%) and 19–36 years age group (74.64%). Regarding vitamin D deficiency status by gender, females were more in numbers 98(80.32%) having deficient in vitamin D levels compared to its male counterparts 29(56.86%), while in insufficiency status was found in 12(9.84%) females and 14(27.45%) males. Vitamin D deficiency is highly prevalent in this study. We recommend evaluation of causal relationship and other risk factors with vitamin D deficiency in a larger sample size. International Journal of Human and Health Sciences Vol. 10 No. 04 Oct’26 Page: 270-273